A Stiff Man-Child Walking: Derrida’s Economy of Secrecy and Faulkner’s “Barn Burning” - Michael Wainwright (European Journal of American Studies)
Working from Jacques Derrida’s contentions about secrecy and authorial responsibility, and paying brief but specific attention to Charles Baudelaire’s “La fausse monnaie” (1869), as suggested by Derridean concerns over capitalist economics, this article studies the manner in which the inviolable and conditional secrets of William Faulkner’s “Barn Burning” (1938) reveal the poststructural tendencies avant la lettre of this leading American modernist.  While Faulkner scholars have focused on the ambivalent language and metaphors deployed in this short story, they have not formerly traced the manner in which “Barn Burning” incites a sense of deconstructive criticism, and have thereby failed to acknowledge Faulkner’s attendant authorial irresponsibility.  This article redresses this critical imbalance.